Isokinetic assessment of muscle strength in female professional soccer athletes - Silva Neto, M.; Simoes, R.; Grangeiro Neto, J. A.; Cardone, C. P. (Revista Brasileira de Medicina do Esporte, 2010)
It has been proved that muscle strength is an important variable to be assessed not only to achieve good performance in sports practice, but also to identify deficits which might put the athlete in a group of higher musculoskeletal injury risk. Few studies to date describe strength values of different joints of elite female soccer players. The objective of this study is to describe those values. For that purpose, twenty-three athletes from the Brazilian national female soccer team, in preparation for the Olympic Games of 2004, were evaluated on an isokinetic dynamometer Cybex 6000 for the following movements: trunk flexion and extension, ,internal and external hip rotation, and knee flexion and extension. The following averages for maximum torque in Nm were found: trunk flexion: 213.2; trunk extension: 267.7; internal hip rotation: 23.1; external hip rotation: 25.6; knee flexion:102.0; knee extension: 181.4. There was no significant difference between the dominant and non-dominant sides. The values found should be considered when the tested individual has similarities with the studied group here.